Ethnic Disparities in Medicare Part D Satisfaction and Intention to Switch Plans. Issue 4 (8th August 2017) - You, Kai; Strawderman, Robert L.; Li, Yue
ABSTRACT: Medicare Part D has been successful in providing affordable prescription drug coverage with relatively high levels of beneficiary reported satisfaction. We use nationally representative survey data to examine whether racial/ethnic disparities exist in reported Part D satisfaction and plan evaluations. Compared to non-Hispanic White Medicare beneficiaries, Hispanic beneficiaries are considerably more likely to report to switch to a new plan in the next year and, among beneficiaries auto-enrolled in a Part D plan, are less likely to be very satisfied with the currently enrolled plan. The findings of ethnic disparities in both Medicare Part D plan satisfaction and the intent to switch plans call for future quality and equity improvement efforts to address these disparities.